The Modulation of the Cell-Cycle: A Sentinel to Alert the NK Cells of Dangers - Vieillard, Vincent; Baychelier, Florence (Frontiers in Immunology, 2013)
Natural killer (NK) cells are an essential component of innate immunity that provides a rapid response to detect stressed, infected, or transformed target cells. This system is controlled by a balance of inhibitory and activating signals transmitted by a myriad of receptors and their specific ligands. Inhibitory receptors mainly recognize self-MHC class-I molecules, whereas activating receptors, such as natural cytotoxic receptors, NKG2D, and DNAM-1, interact with self-proteins, normally not expressed on the cell surface of healthy cells, but up-regulated by cellular stress or infections and are frequently expressed on tumor cells. In these circumstances, regulatory controls ensure that specific ligands are induced mainly in diseased cells and not in normal cells. Each ligand seems to exhibit some distinct specializations providing broad “coverage” for numerous stresses associated with various diseases. Deregulated cell proliferation is a hallmark of these abnormal situations, and may serve as a sentinel for the elimination of the targets by NK cells. The purpose of this review is to discuss recent implications of cell-cycle to create a warning control system that relays various danger signals via specific ligands to the NK receptor system.